2022
DOI: 10.3390/antibiotics11020143
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Carbapenem Consumption and Carbapenems Susceptibility Profiles of Acinetobacter baumannii and Pseudomonas aeruginosa in an Academic Medical Center in Thailand

Abstract: The emergent issue of carbapenem-resistant Acinetobacter baumannii (A. baumannii) and Pseudomonas aeruginosa (P. aeruginosa) is a major problem in Thailand. The wide use of carbapenems can increase selective pressure of bacterial resistance. The objective of this study was to determine the relationship between carbapenem consumption and the susceptibility rates of A. baumannii and P. aeruginosa, including multi-drug resistance (MDR) strains. This was a retrospective study. Carbapenem consumption and susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Although some studies report a correlation between hospital resistance of PAE and carbapenem consumption levels [19], our results echo the findings of Álvarez-Marín et al (2021) showing that the correlation between carbapenem consumption and incidence density of carbapenem-resistant Pseudomonas Aeruginosa is minimal [20]. Importantly, the decrease in consumption of antibiotics was noted to have a greater impact on resistance in the case of Acinetobacter baumanii [8,[21][22][23]. All these findings show that even though antimicrobial selective pressure plays a role in antibiotic resistance [24,25], mechanisms of antimicrobial resistance of are multifactorial (such as carrying resistance genes and other mechanisms) [9,13,26], with a variable role of antimicrobial selective pressure depending on the pathogen, which is akin to the results of other studies [7,9,18,21,27].…”
Section: Discussionsupporting
confidence: 86%
“…Although some studies report a correlation between hospital resistance of PAE and carbapenem consumption levels [19], our results echo the findings of Álvarez-Marín et al (2021) showing that the correlation between carbapenem consumption and incidence density of carbapenem-resistant Pseudomonas Aeruginosa is minimal [20]. Importantly, the decrease in consumption of antibiotics was noted to have a greater impact on resistance in the case of Acinetobacter baumanii [8,[21][22][23]. All these findings show that even though antimicrobial selective pressure plays a role in antibiotic resistance [24,25], mechanisms of antimicrobial resistance of are multifactorial (such as carrying resistance genes and other mechanisms) [9,13,26], with a variable role of antimicrobial selective pressure depending on the pathogen, which is akin to the results of other studies [7,9,18,21,27].…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the same proportion at 70% was found during the pandemic period [ 5 ]. However, the issue of increased antibiotic consumption during the pandemic period is mostly reflected in the proportion of patients being prescribed antibiotics [ 2 , 5 ], where few reported the magnitude of antibiotic utilization in ICU with the measure of DDD [ 3 ], which is also an important indicator for usage trend monitoring, the impact of intervention, global comparison [ 16 ], as well as correlation with resistance trends [ 12 , 17 , 18 ]. The decrease in total ICU admissions was attributed to the opening of the COVID-19 ICU with redistribution of manpower and the closure of the operating theatre elective list during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increase in antimicrobials resistance (AMR) in ICUs was observed since the COVID-19 pandemic, owing to the compromise in infection control and excessive antimicrobials use [ 10 ]. Carbapenems consumption has a positive correlation with increased resistance to carbapenems among gram-negative organisms such as Acinetobacter baumannii , Pseudomonas aeruginosa , and Enterobacterales [ 11 , 12 , 13 ]. Till the year 2020, surveillance in local hospitals of Malaysia reported that resistance to meropenem was lower than 10% for most gram-negative organisms, except Acinetobacter baumannii (58.5%) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…imipenem, meropenem, ertapenem and doripenem), which are often the last safe and effective therapeutic choices in these infections. The correlation between antibiotic use (especially if injudicious) and the prevalence of antimicrobial resistance has been described by numerous studies [ 31 , 32 ]. In addition, shifts in systemic antibiotic consumption may have considerable effects on the epidemiology of infectious agents, both locally and globally [ 33 ].…”
Section: Introductionmentioning
confidence: 99%